2022
DOI: 10.1007/s10875-022-01239-z
|View full text |Cite
|
Sign up to set email alerts
|

TCRαβ-Depleted Haploidentical Grafts Are a Safe Alternative to HLA-Matched Unrelated Donor Stem Cell Transplants for Infants with Severe Combined Immunodeficiency

Abstract: Hematopoietic stem cell transplantation and gene therapy are the only curative therapies for severe combined immunodeficiency (SCID). In patients lacking a matched donor, TCRαβ/CD19-depleted haploidentical family donor transplant (TCRαβ-HaploSCT) is a promising strategy. Conditioned transplant in SCID correlates to better myeloid chimerism and reduced immunoglobulin dependency. We studied transplant outcome in SCID infants according to donor type, specifically TCRαβ-HaploSCT, and conditioning, through retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Because aßTB depletion removes the T cells most closely linked to acute and chronic GVHD and depletes the B cells that can contribute to chronic GVHD, the rates of these complications were anticipated to be lower than that observed after matched donor HCTs despite the increased HLAmismatch. Overall, this has been observed with median rates of grade II-IV aGVHD of 18% (ranging from 11-28%), and cGVHD of 8% (range 0-30%), with 0-21% experiencing extensive cGVHD (129)(130)(131)(132)(133)(134)(135)(136)(137)(138)(139)(140)(141)(142)(143)(144). Notably, most of these studies utilized ATG, which has reduced aGVHD (see above), and not surprisingly, in one study in which ATG was removed, the observed rates of aGVHD were increased (136).…”
Section: Alpha/beta T Cell/b Cell Depletion (Aßtb Depletion)mentioning
confidence: 88%
See 1 more Smart Citation
“…Because aßTB depletion removes the T cells most closely linked to acute and chronic GVHD and depletes the B cells that can contribute to chronic GVHD, the rates of these complications were anticipated to be lower than that observed after matched donor HCTs despite the increased HLAmismatch. Overall, this has been observed with median rates of grade II-IV aGVHD of 18% (ranging from 11-28%), and cGVHD of 8% (range 0-30%), with 0-21% experiencing extensive cGVHD (129)(130)(131)(132)(133)(134)(135)(136)(137)(138)(139)(140)(141)(142)(143)(144). Notably, most of these studies utilized ATG, which has reduced aGVHD (see above), and not surprisingly, in one study in which ATG was removed, the observed rates of aGVHD were increased (136).…”
Section: Alpha/beta T Cell/b Cell Depletion (Aßtb Depletion)mentioning
confidence: 88%
“…Thus, most but not all the studies use this graft engineering approach with related HLA-mismatched donors. This newer therapy has largely been studied in children, comprising 95% of the nearly 700 total patients reported in the literature, and a still small cohort compared to other alternative donor approaches (129)(130)(131)(132)(133)(134)(135)(136)(137)(138)(139)(140)(141). More data is needed to evaluate the success of this approach in adult HCT recipients and would be beneficial in pediatric cohorts as well.…”
Section: Alpha/beta T Cell/b Cell Depletion (Aßtb Depletion)mentioning
confidence: 99%
“…Matched related transplants were associated with the best survival in most studies, while Human Leukocyte Antigen (HLA)-mismatched transplants were associated with worse outcomes [30,35]. Mismatched and even haplo-identical transplants can be performed with lower rates of graft-versus-host disease (GVHD) graft rejection, and survival if the graft is TCRαβ and/or CD19 depleted [31 ▪ ,36 ▪ ,37].…”
Section: Immunodeficiency In Classical Il-2 Receptor Gamma Null Defec...mentioning
confidence: 99%
“…Over the last decade, conditioning regimens have become an increasingly recognized factor in determining long-term immune reconstitution. Myeloablative conditioning or reduced intensity conditioning resulted in higher T-cell counts [19,30] and independence from immunoglobulin [20 ▪ ,30,36 ▪ ]. Poor B-cell reconstitution with lack of memory B cells and persistent humoral dysfunction may be particularly problematic in patients with X-SCID transplanted without conditioning as recipient B cells are unable to respond to IL-21, class switch or differentiate to plasmablasts [15,16,38] (Fig.…”
Section: Immunodeficiency In Classical Il-2 Receptor Gamma Null Defec...mentioning
confidence: 99%
“…One of the advantages of using UCB in the treatment was higher likelihood of B cell engraftment and decreased need for long term IVIG [9] [3], also in contrast to T cell depleted haploidentical and matched unrelated bone marrow transplants [10] [11]. Other advantage of using UCBT in SCID is lower risk of transmitting infections and viral reactivation following engraftment [12], which has been a problem with unrelated donor or TCRαβ-depleted haploidentical HSCT as well as with alemtuzumab conditioning [3,5,13].…”
mentioning
confidence: 99%